2007
DOI: 10.1111/j.1365-2672.2007.03386.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of OmpK, GAPDH and their fusion OmpK-GAPDH derived from Vibrio harveyi outer membrane proteins: their immunoprotective ability against vibriosis in large yellow croaker (Pseudosciaena crocea)

Abstract: Aim:  To investigate the immunoprotection of three recombinant proteins derived from the Vibrio harveyi outer membrane proteins (OMPs) OmpK, glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) and their fusion OmpK–GAPDH as vaccine candidates from vibriosis of large yellow croaker (Pseudosciaena crocea). Methods:  The ompK gene, of which the leader sequence was omitted, was fused with the gapdh gene. Three recombinant proteins r‐OmpK, r‐GAPDH and r‐OmpK–GAPDH were expressed and purified. Western blots were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…Additionally, GAPDH is a common enzyme that exists in many organisms (Liu et al, 2005). Recent investigations of cell surface proteins of pathogenic streptococci and Gram-negative bacteria identified a cellwall-associated protein as structurally and functionally belonging to the GAPDH family of enzymes (Brassard et al, 2004;Hughes et al, 2002;Liu et al, 2005Liu et al, , 2007Sirover, 1999;Zhang et al, 2007). These studies demonstrated that GAPDH is well conserved among species.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Additionally, GAPDH is a common enzyme that exists in many organisms (Liu et al, 2005). Recent investigations of cell surface proteins of pathogenic streptococci and Gram-negative bacteria identified a cellwall-associated protein as structurally and functionally belonging to the GAPDH family of enzymes (Brassard et al, 2004;Hughes et al, 2002;Liu et al, 2005Liu et al, , 2007Sirover, 1999;Zhang et al, 2007). These studies demonstrated that GAPDH is well conserved among species.…”
Section: Discussionmentioning
confidence: 84%
“…Only the attenuated vaccine for E. ictaluri is commercially available in the USA. Moreover, recent reports indicated that an OMP, like GAPDH, from E. tarda is an effective vaccine candidate against E. tarda, V. anguillarum, and V. harveyi in fish (Liu et al, 2005Zhang et al, 2007). However, the efficacy of the GAPDH vaccine from E. ictaluri has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations